2022
DOI: 10.1073/pnas.2109448119
|View full text |Cite
|
Sign up to set email alerts
|

Pten heterozygosity restores neuronal morphology in fragile X syndrome mice

Abstract: Significance Phosphatase and tensin homolog protein (PTEN) and fragile X mental retardation protein (FMRP) play a vital role in neuronal development and function. This work provides new evidence for the genetic interaction of Pten and Fmr1 in postnatal development of granule neurons and conserved mechanisms across evolution. The observed cellular phenotypic defects in Pten and Fmr1 knockout (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Increasing evidence links PTEN to neurodevelopmental and neurodegenerative diseases [44,45]. PTEN translation is negatively regulated by FMRP and heterozygous loss of Pten rescued neuronal phenotypes in an Fmr1 knockout mouse [55]. Moreover, it has been shown that PTEN knockdown or pharmacological inhibition is beneficial for MN survival and neuromuscular innervation in non-FUS ALS and spinal muscular atrophy models [46][47][48]56].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence links PTEN to neurodevelopmental and neurodegenerative diseases [44,45]. PTEN translation is negatively regulated by FMRP and heterozygous loss of Pten rescued neuronal phenotypes in an Fmr1 knockout mouse [55]. Moreover, it has been shown that PTEN knockdown or pharmacological inhibition is beneficial for MN survival and neuromuscular innervation in non-FUS ALS and spinal muscular atrophy models [46][47][48]56].…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is a master inhibitor of cell growth, survival, and differentiation (Tariq et al, 2022). Overexpression of PTEN leads to reduced neuronal growth, axon growth, and dendritic branching (Sathyanarayana et al, 2022). Moreover, inhibition of PTEN following middle cerebral artery occlusion (MCAO) improved neuronal survival, dendritic arborization, and motor deficits (Mao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The PTEN protein is part of a signaling network that contains multiple autism spectrum disorder (ASD)-associated gene products and represents a potentially common etiological mechanism for ASD and related neurodevelopmental disorders (Rademacher et al, 2019;Cummings et al, 2022). PTEN translation is negatively regulated by FMRP and heterozygous loss of Pten rescued neuronal phenotypes in a Fmr1 knockout mouse (Sathyanarayana et al, 2022). Moreover, it has been shown that PTEN knockdown by RNA interference is beneficial for MN survival in SOD1-and C9ORF72-ALS and spinal muscular atrophy models (Kirby et al, 2011;Little et al, 2015;Stopford et al, 2017).…”
Section: Discussionmentioning
confidence: 99%